(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Customer satisfaction is a critical factor in the success of any industry, and the Indian automobile industry is no exception. This research paper aims to explore the various factors influencing customer satisfaction in the Indian automobile industry